'Annotation and choreographic self-awareness'. Issue 1 (2nd January 2021) - Piquero-Alvarez, Lucía
ABSTRACT: Through my doctoral research I developed a form of annotation and analysis of works to explore experiences of emotion in contemporary theatre dance. This approach helped me analyse works by different choreographers and share my spectatorial experience of them. To explore whether the work had emotional information embodied in its perceptual properties, I analysed movement qualities, movement-music, and spatial-rhythm. Through these analysis I was able to understand aspects of my process which were not obvious before. The analysis seemed to improve my choreographic self- awareness. Scholars such as Sarah Whatley have pointed at the potential of documenting, sharing, and curating information about choreographic practices, and its use as feedback tool for the choreographers [Whatley, Sarah. 2018. "Enhancing Choreographic Objects; Traces, Texts and Tales of a Journey Through Dance." In Performing Process Sharing Dance and Choreographic Practice, edited by Hetty Blades and Emma Meehan, 67–80. Bristol: Intellect]. But what happens when the analyst and the choreographer are the same person? For me, the process became a form of self-discovery. This article is a reflection on the difficulties, implications, and repercussions of undertaking a systematic analysis/annotation of my work, especially in relation to emotion.